FEATURES OF THE STEREOMORPHOLOGY OF THE HUMAN PANCREAS IN AGE ASPECT - Пелипенко, Л.Б.; Шепітько, В.І.; Єрошенко, Г.А.; Лисаченко, О.Д. (World of Medicine and Biology, 2016)
As a result of the stereomorphologicalanalysis of newborn and adult pancreas it is proved that they are isomorphic functional systems with minor differences in the structure. From the combination of morphological characters, the newborn human pancreas gland refers to a fully developed bifunctional body. Structural and functional unit is allocated a lobe, which, unlike an adult, with respect to the volume of the interstitial space is dominated by more developed network of blood microvessels density and lower exocrine cells in the end-pieces.